Komunikasi Budaya Santri di pondok Pesantren Riyadhul Awwamil - Amelia Febriyanti; Ilah Holilah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The cultural communication of santri at Pondok Pesantren Riyadhul Awamil, a pesantren that integrates classical Islamic traditions with the dynamics of modern santri life, serves as the central theme of this study. The main focus is to examine how communication patterns are formed and practiced among santri, between santri and the kiai (Islamic teacher), and within the broader pesantren environment. The study employs a qualitative approach through field observation and in-depth interviews with key informants. The findings indicate that the communication culture within this pesantren is strongly influenced by Islamic values such as adab (etiquette), tawadhu (humility), and the spirit of ukhuwah (brotherhood). The language used is not only verbal but also symbolic, expressed through daily traditions such as studying classical Islamic texts (kitab kuning), acts of service (khidmat), and group discussions (musyawarah). This cultural communication functions not only as a means of conveying religious messages but also as a tool for shaping the character and identity of the santri. The study concludes that the cultural communication of santri at Pondok Pesantren Riyadhul Awamil plays a vital role in preserving pesantren values while serving as an effective medium of Islamic propagation both within and beyond the pesantren community.